Characteristics of the transformations occurred within the intercritical interval of ductile iron - Basso, Alejandro Daniel (2010)
Austempered Ductile Iron (ADI) and fully ferritic ductile iron are frequently used to produce safety parts. A new kind of ductile iron (DI), usually referred to as “dual phase ADI” is currently under development. The matrix of this new material is composed of ausferrite (regular ADI microstructure) and free (or allotriomorphic) ferrite. This combined microstructure is obtained by subjecting DI to heat treatments comprising incomplete austenitization stages at temperatures within the intercritical interval (three phase α-γ-Gr field of the Fe-C-Si stable diagram) followed by an austempering step in a salt bath in order to transform the austenite into ausferrite. This work describes some alternatives to control morphologies and amounts of phases present in the final microstructure. A revision of the results obtained on this matter by the authors as well as by other researchers is also provided. A ductile iron melt was produced in a metal casting laboratory. Samples were heat treated following different thermal cycles to obtain a wide range of duplex microstructures, containing different amounts and morphologies of microconstituents. The results account for the fact that the transformations occurring within the α-γ-Gr field are strongly affected by the chemical composition, previous matrix, and holding times. The role played by the microsegregation and availability of sites for heterogeneous nucleation is also worth noticing. Starting from ferritic matrices and holding the samples at constant temperature within the intercritical interval, austenite nucleation and growth take place mainly in the last to freeze zones. On the other hand, when starting from fully recrystallised austenitic matrices, allotriomorphic ferrite can precipitate during the isothermal holding within the intercritical interval at the austenite grains boundaries forming a continuous net. The kinetics of the γ α transformation is notoriously slower than the α γ one. The influence that part size exerts on the final microstructure is also analyzed.